Innovative Applications and Challenges of Multimodal Artificial Intelligence Technology - Chen, Dong (Innovative Applications of AI, 2025)
With the continuous evolution of artificial intelligence technology, multimodal artificial intelligence technology has come to the fore, becoming a research hotspot in the field. This paper delves into the innovative applications of multimodal artificial intelligence technology and comprehensively analyzes the challenges it faces in practical applications. By sorting through key technologies such as multimodal data fusion and feature extraction, and combining rich practical cases, the paper showcases the outstanding performance of this technology in various fields such as healthcare, education, and intelligent security. Research indicates that multimodal artificial intelligence technology has significant advantages in enhancing system intelligence levels and improving human-machine interaction experiences, but it also faces challenges such as the complexity of data processing and the difficulty of model training. This paper aims to provide theoretical support and practical guidance for the further development of multimodal artificial intelligence technology, promoting its widespread application in more fields.